The Role of Transformational Leadership in The Implementation of Organizational Strategic Management - Sugianto, Efendi; Suhardi, Suhardi; Afrizal, Afrizal (Cognitionis Civitatis et Politicae, 2025)
Leaders and Leadership are very strategic factors in an organization. The Leadership process in an organization occurs because of the element of a leader, the organization must be seen as a system with open leadership characteristics and leadership is a strategic factor in an organization. Transformative leadership impacts strategic management outcomes by influencing strategy content and subsequently organizational outcomes. Leaders are critical in integrating tensions within organizations because their characteristics and actions shape strategic direction. Merging tensions requires new management principles, practices, and structures, known as management innovation. These innovations introduce new management approaches to achieve organizational goals and sustain transformative strategies. By guiding organizations through structured flexibility and facilitating the merging of tensions, transformative leaders play a critical role in driving strategic management outcomes toward success. Communication is essential to implementing strategic management, serving as a crucial channel for aligning organizational goals, facilitating change, and ensuring effective strategy execution. The author’s research provides a comprehensive view of how transformational leadership influences the implementation of strategic management in various contexts. Strategic management is critical to aligning organizational goals, effective communication ensures that all stakeholders, including employees, management, and external partners, understand the strategic vision and their role within it, this alignment is critical to fostering unified direction and commitment toward achieving strategic goals.